CULTURAL DIVERSITY AND ITS MANAGEMENT IN PRIMARY SCHOOLS ACCORDING TO THE TYPOLOGY OF THE EDUCATIONAL CENTRES. THE CASE OF SOUTHERN SPAIN - Luque, Mónica; Venegas, Mar; Velasco, Elisa; Sánchez-Miranda, Kiko (Revista Lusófona De Educação, 2026)
This research focuses on southern Spain, specifically in the regions of Andalusia, Murcia, Ceuta and Melilla. It aims to analyse the strategies that primary schools implement with students and families in relation to cultural diversity in their activities to promote intercultural social interactions. The main objective is to look at the differences between schools according to types of school, i.e. whether they are public or private schools, or private subsidised schools. This research is part of the projects corresponding to the State Programme R+D+i Oriented to the Challenges of Society. A quantitative methodology was used to carry out this study, based on one-factor ANOVA and Student's t-test. The sample consisted of 420 respondents among school management staff. The results show statistically significant differences in the inclusion of cultural diversity activities in the school curriculum, in textbooks and in intercultural education as a reference point in schools.
Diversidade cultural e a sua gestão nas escolas do ensino básico segundo a tipologia dos estabelecimentos de ensino: o caso do sul de Espanha
La diversité culturelle et sa gestion dans les écoles primaires selon la typologie des établissements scolaires : le cas du sud de l’Espagne.
Keywords: cultural diversity; interculturality; social interaction; types of school